Supramolecular Assembly of Self‐Healing Nanocomposite Hydrogels. Issue 24 (27th October 2014) - Gerth, Marieke; Bohdan, Malgorzata; Fokkink, Remco; Voets, Ilja; van der Gucht, Jasper; Sprakel, Joris
<x xml:space="preserve">Abstract</x> Hierarchical self‐assembly of transient composite hydrogels is demonstrated through a two‐step, orthogonal strategy using nanoparticle tectons interconnected through metal–ligand coordination complexes. The resulting materials are highly tunable with moduli and viscosities spanning many orders of magnitude, and show promising self‐healing properties, while maintaining complete optical transparency. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>